Experimental evaluation of a heat pipe cooled structured reactor as part of a two-stage catalytic methanation process in power-to-gas applications. (1st November 2018) - Neubert, Michael; Hauser, Alexander; Pourhossein, Babak; Dillig, Marius; Karl, Juergen
Graphical abstract: Highlights: Literature review on recent demonstration projects concerning structured and micro-structured reactors. Novel and innovative integration of heat pipes in a structured reactor for methanation. Extensive experimental work and proof-of-concept. Grid-injectable SNG in lab-scale two-stage experimental setup. Abstract: Establishing the power-to-gas process as a suitable energy storage in future energy systems requires process simplification in order to make it competitive. An intensified methanation reactor concept could contribute to this overall goal. The present work suggests a new catalytic methanation reactor with heat pipe integration into a structured reactor. This approach benefits from the highly industrial maturity of the methanation process and simultaneously addresses the requirements of new applications in power-to-gas processes. The concept comprises a metallic body, which is perforated by channels for internal gas preheating, reaction channels and spaces for the incorporation of heat pipes. Calculation of the radial temperature profiles provided the limits for the channel geometry. Three layers of internal manifolds at different heights distribute, collect and divert the gas. Heating cartridges integrated at the bottom of the reactor enable rapid start up from cold conditions. The metallic block structure facilitates the sealing of the pressurized reaction space and the scaling. First experiments with a 5 kW prototype prove that the maximum temperature is kept more than 100 K below calculated adiabatic synthesis temperatures. Furthermore, the integration in a lab-scale two-stage test rig with intermediate water removal demonstrates the Substitute Natural Gas (SNG) production with grid-injectable quality.